Tropical African studies (International Library of African Music, 1964)
The International African Institute in conjunction with the University of Ibadan, held a Conference on Tropical African Studies, from the 5th to the 11th April, 1964. One section of this Conference was devoted to the Arts in African Studies, and the following report is taken from their published report on the Conference in Volume 35, No. 1, of Africa, for January, 1965. The subjects under discussion were the scope and development of studies in the visual arts, music and literature; their relation to other fields in African studies and further needs in research and teaching.
Keywords: African Music